Somatic cell count inversely related to potential profits in dairying - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1992)
Somatic Cell Count (SCC) affects productivity of a dairy herd and, thus, potential profit. Almost all SCC problems can be solved by management. The DHIA SCC program is very useful for evaluating the situation in a dairy herd to solve such problems.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; Somatic cell count; Mastitis; Rolling herd average